PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN SMART BOX LITERASI TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS I SDN JURUREJO 2 - Ema Ipenda; Novia Rahma Rista Utami; Desi Nuzul Agnafia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The purpose of using this learning media is so that learning activities can runoptimally and student learning outcomes increase. Seeing at SDN Jururejo 2,especially class I, class teachers still use minimal aids in the learning process orwhat is commonly called learning media and causes student learning outcomes tobe below the KKM. This thesis discusses the Influence of Smart Box LiteracyLearning Media on Indonesian Language Learning Outcomes for Class I Studentsof Syllable Material at SDN Jururejo 2. This study uses a quantitative researchmethod with the type of One Group Pretest - Posttest research. Design. Thepopulation and sample in this study were all class I students of SDN Jururejo 2.The data collection technique used was a written test. The data collectiontechnique used tests and non-participation observations. The research instrumentused a pretest and posttest. Data analysis used several tests including instrumenttests, prerequisite analysis tests and hypothesis tests. The results of this studywere that in the instrument test there were 20 questions that could be used andthe researcher used all of these questions for data collection. Next is the analysisprerequisite test, namely there is a normality test, the normality test obtainedpretest results with a significant value of 0.167 > 0.05 and posttest 0.138 > 0.05,ending with a hypothesis test using the paired sample t-test. In this paired samplet-test, the sig (2-tailed) results were obtained, namely 0.000, 0.05, so it can beconcluded that Ho is rejected and Ha is accepted.Keywords: Learning Media, Smart Box, Learning Outcomes